Thyrotoxic hypokalemic periodic paralysis as the initial manifestation of graves’ disease - Fidan Çolak, Tuğçe; Muradkhanova, Shams; Doğan, Baki; Güngör, İbrahim Levent (Acta Medica, 2025)
Thyrotoxic periodic paralysis (TPP) is a rare, potentially life-threatening condition characterized by acute, symmetrical paralysis of proximal muscles coupled with severe hypokalemia, typically arising in the context of thyrotoxicosis, often associated with Graves’ disease. We present a case of a 41-year-old male who exhibited sudden-onset quadriplegia following a week of muscle cramps. Initial assessments revealed profound hypokalemia (1.4 mEq/L) and electrocardiographic abnormalities consistent with arrhythmias. Diagnosis was confirmed through positive thyrotropin receptor antibodies and ultrasound findings indicating Graves’ disease. The patient was treated with methimazole and propranolol, along with immediate potassium replacement. Remarkably, his motor function improved dramatically post-treatment, with normalization of ECG findings before discharge, highlighting the prompt responsiveness to management and the need for timely diagnosis of this condition. Given the serious implications of untreated hypokalemic periodic paralysis, including respiratory failure and cardiac complications, clinicians must maintain a high index of suspicion for TPP in patients presenting with acute muscle weakness and hypokalemia.